1. The problem statement, all variables and given/known data Solve the given differential equation subject to the indicated initial condition. (e^-y + 1)sinxdx=(1+cosx)d, y(0)=0 2. Relevant equations Basically we have to use seperation of varaibles to solve before using initial value condition. 3. The attempt at a solution After separation of variables Dy/(e^-y +1) = sinx dx/(1+cosx) take the integral of both sides ∫Dy/(e^-y +1)=ln|e^-y+1|+y ∫sinx dx/(1+cosx)= -ln(1+cosx)+c Clean it up a bit ln|e^-y+1|+y= -ln(1+cosx)+c I have no idea what to do now with the y(0)=0 That means plus in x=0 for the equation correct?